Asuhan Keperawatan Pemenuhan Kebutuhan Aman Nyaman Dengan Pemberian Kompres Hangat Untuk Mengurangi Nyeri Pada Klien Hipertensi Di Tatanan Keluarga - Aprilya, Dea; Dwi Pramesti, Anastasya (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Background: Hypertension is a prevalent non-communicable health problem that can lead to complications. One of the early symptoms experienced by individuals with hypertension is headaches that can occur in the neck and head area. Managing hypertension-induced headaches can be achieved through non-pharmacological methods, such as using warm compresses. Objective: This study aims to provide an overview of nursing care for hypertensive patients in a family setting, focusing on the application of warm compresses to alleviate pain and meet their safe and comfortable needs. The warm compresses were administered twice a day for 15 minutes. Methods: A case study was conducted involving descriptive analysis of 2 clients over a period of 3 days. Results: Following the implementation of warm compresses for 3 days, it was observed that client 1 experienced a reduction in pain scale from a level of 5 (moderate) to a level of 1 (mild), while client 2 experienced a decrease from a level of 5 (moderate) to a level of 0 (no pain). Conclusion: By providing nursing care, it is hoped that clients can continue using warm compresses as a non-pharmacological method to alleviate pain.